Perivascular Adipose Tissue-Derived Adiponectin Inhibits Collar-Induced Carotid Atherosclerosis by Promoting Macrophage Autophagy - Li, Changlong; Wang, Zhijian; Wang, Chunxiao; Ma, Qian; Zhao, Yingxin (PloS one, 2015)
Adiponectin (APN) secreted from perivascular adipose tissue (PVAT) is one of the important anti-inflammatory adipokines to inhibit the development of atherosclerosis, but the underlying mechanism has not been clarified. In this study, we aimed to elucidate how APN regulates plaque formation in atherosclerosis. To assess the role of APN secreted by PVAT in atherosclerosis progression, we performed PVAT transplantation experiments on carotid artery atherosclerosis model: ApoE knockout (ApoE-/-) mice with a perivascular collar placement around the left carotid artery in combination with a high-fat diet feeding. Our results show that the ApoE-/- mice with PVAT derived from APN knockout (APN-/-) mice exhibited accelerated plaque volume formation compared to ApoE-/- mice transplanted with wild-type littermate tissue. Conversely, autophagy in macrophages was significantly attenuated in ApoE-/- mice transplanted with APN-/- mouse-derived PVAT compared to controls. Furthermore, in vitro studies indicate that APN treatment increased autophagy in primary macrophages, as evidenced by increased LC3-I processing and Beclin1 expression, which was accompanied by down-regulation of p62. Moreover, our results demonstrate that APN promotes macrophage autophagy via suppressing the Akt/FOXO3a signaling pathway. Our results indicate that PVAT-secreted APN suppresses plaque formation by inducing macrophage autophagy.